Gambaran Postur Kerja dan Keluhan Musculoskeletal Disorders (MSDs) pada Pekerja Bangunan Bangunan di PT Q6 - I Komang Ary Setia Kurniawan; Ni Wayan Rusni; Komang Trisna Sumadewi (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
Musculoskeletal disorders (MSDs) are disorders related to various components in the human body, including muscles, tendons, ligaments, cartilage, nervous system, bone structure, and blood vessels, which are often found in construction workers with poor posture while working. MSDs affect almost 1.71 billion people worldwide. Construction workers are one of the professions contributing to the high number of MSDs incidents. The purpose of this study was to determine the description of work posture and MSDs in construction workers at PT Q6. We employed a descriptive, cross-sectional method, utilizing primary data from the July 2024 research at PT Q6. We conducted this study on 70 samples. The results of the study were dominated by work postures with minimal risk (50%), MSDs were dominated by high-risk complaints (70%), the age of workers was dominated by <35 years (51.4%), all workers were male (100%), the dominant work duration was ? 8 hours (80%), MSDs in the age category <35 years were dominated by high risk (55.1%), MSDs in the work duration category <8 hours were dominated by both moderate (95.2%) and high (73.5%) risk, and MSDs in men were dominated by moderate (100%) and high (100%) risk categories. The conclusion of the study shows that the working posture of construction workers at PT Q6 generally has minimal risk, while MSDs occur most often at high risk. Further research suggestions include excluding individuals over 55 years of age and controlling for confounding factors.